Industrial Relations in Canadian Industries - Harcourt, J. Mark (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "Industrial Relations in Canadian Industries," edited by Richard P. Chaykowski and Anil Verma.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z